2021
DOI: 10.1007/s40692-021-00191-y
|View full text |Cite
|
Sign up to set email alerts
|

How higher education students in Egypt perceived online learning engagement and satisfaction during the COVID-19 pandemic

Abstract: This study aims to examine the influence of academic self-efficacy, perceived usefulness of online learning systems, and teaching presence on student engagement (behavioural, emotional, and cognitive engagement) and student satisfaction with online learning. Data were collected from undergraduate students who experienced a fully online learning process during the COVID‐19 pandemic. Based on social cognitive theory, the relationships among the personal and environmental influences on student behaviour and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 63 publications
13
122
3
3
Order By: Relevance
“…The findings also provide further evidence for Kim and Kim (2021) that student engagement is a key factor in enhancing students' desirable learning outcomes, positively associated with student online learning satisfaction. In accordance with the previous studies, those students who are engaged in the learning process tend to invest more during their learning, participate more in learning activities, and tend to develop mechanisms to assist them in achieving their academic goals (Klem and Connell, 2004) and leading to more satisfaction in both faceto-face and online context learning (Coetzee and Oosthuizen, 2012;El-Sayad et al, 2021). Finally, this study confirmed the partial mediation role of academic self-efficacy and student engagement in the relationship between interaction and online learning satisfaction (Q5).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The findings also provide further evidence for Kim and Kim (2021) that student engagement is a key factor in enhancing students' desirable learning outcomes, positively associated with student online learning satisfaction. In accordance with the previous studies, those students who are engaged in the learning process tend to invest more during their learning, participate more in learning activities, and tend to develop mechanisms to assist them in achieving their academic goals (Klem and Connell, 2004) and leading to more satisfaction in both faceto-face and online context learning (Coetzee and Oosthuizen, 2012;El-Sayad et al, 2021). Finally, this study confirmed the partial mediation role of academic self-efficacy and student engagement in the relationship between interaction and online learning satisfaction (Q5).…”
Section: Discussionsupporting
confidence: 77%
“…That is to say, university students who interact more are likely to foster their academic self-efficacy (Gebauer et al, 2020). Subsequently, with higher academic self-efficacy, they believe that they have sufficient ability to perform online tasks and are more engaged with their learning (El-Sayad et al, 2021), which in turn contribute to their satisfaction in online learning (Kim and Kim, 2021). This study also gives rise to several important implications for better understanding students' satisfaction in the online learning context during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 78%
“…The COVID-19 outbreak has brought the research on online learning satisfaction to a climax. El-Sayad et al (2021) explored the relationship between students' participation and their satisfaction with online learning from the perspective of students, and showed that there is a positive impact on their online learning satisfaction. Ramón et al (2021) have the same view.…”
Section: Parent Satisfactionmentioning
confidence: 99%
“…Emotional engagement refers to the emotional attitude and recognition of the school and belongingness. Cognitive engagement refers to the self-regulation method of learning and using post-cognitive strategies ( Fredricks et al, 2004 ; El-Sayad et al, 2021 ). The participants in this study were well aware of cram school behavioral engagement ( M = 3.75, SD = 0.84), emotional engagement ( M = 3.44, SD = 0.68), and cognitive engagement ( M = 3.52, SD = 0.71).…”
Section: Resultsmentioning
confidence: 99%